Race to the Top: evaluation of a novel performance-based financing initiative to promote healthcare delivery in rural Rwanda. Issue 1 (1st December 2016) - Nahimana, Evrard; McBain, Ryan; Manzi, Anatole; Iyer, Hari; Uwingabiye, Alice; Gupta, Neil; Muzungu, Gerald; Drobac, Peter; Hirschhorn, Lisa R.
Abstract : Background: Performance-based financing (PBF) has demonstrated a range of successes and failures in improving health outcomes across low- and middle-income countries. Evidence indicates that the success of PBF depends, in large part, on the model selected, in relation to a variety of contextual factors. Objective: Partners In Health∣Inshuti Mu Buzima aimed to evaluate health outcomes associated with a novel capacity-building model of PBF at health centers throughout Kirehe district, Rwanda. Design: Thirteen health centers in Kirehe district, which provide healthcare to a population of over 300, 000 people, agreed to participate in a PBF initiative scheme that integrated data feedback, quality improvement coaching, peer-to-peer learning, and district-level priority setting. Health centers' progress toward collectively agreed upon site-specific health targets was assessed every 6 months for 18 months. Incentives were awarded only when health centers met goals on all three priorities health centers had collectively agreed upon: 90% coverage of community-based health insurance, 70% contraceptive prevalence rate, and zero acute severe malnutrition cases. Improvement across all four time points and facilities was measured using mixed-effects linear regression. Findings: At 6-month follow-up, 4 of 13 health centers had met 1 target. At 12-month follow-up, 7 centers had met 1 target, and by 18-month follow-up, 6 centers had met 2 targets and 2 centers had met all 3. Average health center performance had improved significantly across the district for all three targets: mean insurance coverage increased from 68% at baseline to 93% ( p <0.001); mean number of acute malnutrition cases in the previous 6 months declined from 24 to 5 per facility ( p <0.001); and contraceptive prevalence increased from 42 to 59% ( p <0.001). A number of innovative improvement initiatives were identified. Conclusion: The combining of PBF, district engagement/support, and peer-to-peer learning resulted in significant improvements despite resource constraints and is now being considered as a model for scale-up in other districts of Rwanda.